SOCIO-CULTURAL AND RELIGIOUS EXPLORATION OF THE MARRIAGE PRACTICES OF OHAFIA PEOPLE IN ABIA STATE - Ohazurume, Uche Christian; Ottuh, Peter Oghenefavwe (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
ABSTRACTThis study examines the social and religious perspectives, as well as the cultural aspects, of marriage practices among the Ohafia people of Abia State, Nigeria. In Ohafia society, marriage is not just a bond between two individuals; it also involves families, lineage considerations, economic duties, religious obligations, and social responsibilities. By employing qualitative research methods and reviewing existing literature, the study examines various aspects of traditional marriage, including the roles of family and kinship, economic considerations, gender expectations, and the influence of religion on marriage practices. The findings show that Ohafia marriage involves courtship, family introduction, bride-wealth negotiation, traditional ceremonies, and life after marriage, all guided by community values, ritual customs, and ancestral approval. Bride price, gifts, and community work validate marriages and strengthen ties between families. Gender roles reflect complementary duties, which maintain stability and unity. The study also notes the influence of modern trends on current marriage practices. Therefore, marriage in Ohafia society continues to be a key instrument for reinforcing social values, moral behavior, and cultural identity. Based on these insights, recommendations are offered for preserving cultural practices, promoting gender equality, encouraging sustainable economic practices, educating youth, and conducting further research on changing marriage systems.